PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI KANTIN FAPERTA UR - Sartika, Wahyu; Dewi, Novia; Restuhadi, Fajar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Consumer assessment in a purchase is influenced by the perceived personal interests or incurred by the conditions that must be decided choice to set the right choice of the needed product. This study aims to analyse the influence marketing mix (4P) on consumer purchasing decisions at Faperta UR's canteen and knows of the fourth marketing mix (4P), which is the most dominant influence consumer purchasing decision at Faperta UR's canteen. Sample in this study amounted to 184 respondents. Data were analyzed using of structural equation modeling (SEM). Analysis shows the marketing mix variables of product, price, place, and promotion, of the four marketing mix that is variable with a value of 54.10%. Indicator consists of a location canteen close to the campus and delivery. Keyword: Marketing mix, Consumer decision, Structural Equation Modeling (SEM)